Comorbidity increases the risk of hospitalizations in multiple sclerosis - Marrie, Ruth Ann (Neurology, 2015)
OBJECTIVE: We aimed to evaluate the association between comorbidity and rates of hospitalization in the multiple sclerosis (MS) population as compared to a matched cohort from the general population. METHODS: Using population-based administrative data from the Canadian province of Manitoba, we identified 4,875 persons with MS and a matched general population cohort of 24,533 persons. We identified all acute care hospitalizations in the period 2007–2011. Using general linear models, we evaluated the association between comorbidity status and hospitalization rates (all-cause, non-MS-related, MS-related) in the 2 populations, adjusting for age, sex, and socioeconomic status. RESULTS: Comorbidity was common in both cohorts. Over the 5-year study period, the MS population had a 1.5-fold higher hospitalization rate (adjusted rate ratio [aRR] 1.56; 95% confidence interval [CI] 1.44–1.68) than the matched population. Any comorbidity was associated with a 2-fold increased risk of non-MS-related hospitalization rates (aRR 2.21; 95% CI 1.73–2.82) in the MS population, but a nearly 4-fold increase in hospitalization rates in the matched population (aRR 3.85; 95% CI 3.40–4.35). Comorbidity was not associated with rates of hospitalization for MS-related reasons, regardless of how comorbidity status was defined. CONCLUSIONS: In the MS population, comorbidity is associated with an increased risk of all-cause hospitalizations, suggesting that the prevention and management of comorbidity may reduce hospitalizations.